2020
DOI: 10.3892/ijo.2020.5089
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress, unfolded protein response and autophagy contribute to resistance to glucocorticoid treatment in human acute lymphoblastic leukaemia cells

Abstract: Acute lymphoblastic leukaemia (ALL) is the most frequent childhood cancer and, although it is highly treatable, resistance to therapy, toxicity and side effects remain challenging. The synthetic glucocorticoid (GC) dexamethasone (dex) is commonly used to treat ALL, the main drawback of which is the development of resistance to this treatment. The aim of the present study was to investigate potential molecular circuits mediating resistance and sensitivity to GC-induced apoptosis in ALL. The leukaemia cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…As mentioned, the role of autophagy in tumor development is controversial and dependent of the tumor characteristics and stage of tumor development (266). Briefly, it has been suggested that autophagy could promote aggressive characteristics of cancer cells such as increased cellular invasion (11,12), but it also represents a barrier for cancer proliferation (13)(14)(15). In cancer cells, the inhibition of autophagy results in impaired metabolism proliferation, survival, and spontaneous tumor malignancy depending not only on the tumor type but also of its temporal development (267).…”
Section: Role Of Autophagy In Vascular Remodeling In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned, the role of autophagy in tumor development is controversial and dependent of the tumor characteristics and stage of tumor development (266). Briefly, it has been suggested that autophagy could promote aggressive characteristics of cancer cells such as increased cellular invasion (11,12), but it also represents a barrier for cancer proliferation (13)(14)(15). In cancer cells, the inhibition of autophagy results in impaired metabolism proliferation, survival, and spontaneous tumor malignancy depending not only on the tumor type but also of its temporal development (267).…”
Section: Role Of Autophagy In Vascular Remodeling In Cancermentioning
confidence: 99%
“…Indeed, the role of autophagy in tumor development is controversial and dependent on tumor stage and type. It has been suggested that autophagy could promote aggressive characteristics of cancer cells, such as increased cellular invasion (11,12), but also be a barrier to cancer proliferation (13)(14)(15). Additionally, autophagy also provides the microenvironment for placentation and cancer growth.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation therapy was capable of activating stress adaptation responses that involve the ER 17 . Investigators have paid attention to alterations that occur in ER stress 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Leukemia is characterized by the accumulation of gene mutations and chromosomal translocations that the encoding proteins are frequently prone to misfolding ( 23 , 44 , 45 ). It has been reported that sustained UPR exists in multiple leukemia types and plays a vital role in disease progression and therapeutic resistance ( 19 , 20 , 46 48 ). Thus, targeting ER stress and UPR mechanisms represents attractive therapeutic options to the leukemia treatment ( 49 53 ).…”
Section: Discussionmentioning
confidence: 99%